THE IMPLEMENTATION OF AQIKAH AND ITS EDUCATIONAL VALUES IN A REVIEW OF CLASSICAL ISLAMIC LAW - Muchlis Bahar (Jurnal Kelola: Jurnal Ilmu Sosial, 2019)
The purpose of this study is to analyze the implementation of Aqiqah and its educational value in a review of classical Islamic law. The method in this study is a qualitative method with a descriptive analysis approach. The type of data used in this research is secondary data, the data is collected through the literature study method. The analysis and presentation of data in this study used a descriptive method. Based on the results of the analysis, it can be concluded that the law of Aqiqah is Sunnah Mu-akkadah, Aqiqah is carried out on the seventh day of the birth of the baby, or the fourteenth, or twenty-first day, some scholars allow until the end of the postpartum blood of the mother (approximately 40th day), when the baby is an adult, the obligation to carry out the Aqiqah falls. There are several educational values ​​in the aqiqah law, namely faith education; The role of parents is very important as the first and foremost educator in instilling faith education in children. Moral Education; from giving a good name, the meaning is to make it easier to call him, and avoid calls that are not clear, then the name is a prayer for the child and as his identity, and health education.